Assessment of controlling processes for field‐scale uranium reactive transport under highly transient flow conditions. Issue 2 (6th February 2014) - Ma, Rui; Zheng, Chunmiao; Liu, Chongxuan; Greskowiak, Janek; Prommer, Henning; Zachara, John M.
Abstract: This paper presents the results of a comprehensive model‐based analysis of a uranyl [U(VI)] tracer test conducted at the U.S. DOE Hanford 300 Area (300A) IFRC. Despite the highly complex field conditions the numerical three‐dimensional multicomponent reactive transport model was able to capture most of the spatiotemporal variations of the observed U(VI) concentrations. A multimodel analysis was performed to interrogate the relative importance of various processes and factors for controlling field‐scale reactive transport during the uranyl tracer test. The results indicate that multirate sorption/desorption, surface complexation reactions, and initial concentration distributions were the most important processes and factors controlling U(VI) migration. On the other hand, cation exchange reactions, the choice of the surface complexation model, and dual‐domain mass transfer processes played less important roles under the prevailing field‐test conditions. Further analysis of the modeling results demonstrates that these findings are conditioned to the relatively stable groundwater chemistry and the selected length of the field experimental duration (16 days). The model analysis also revealed the crucial role of the intraborehole flow that occurred within the long‐screened monitoring wells and thus affected both field measurements and simulated U(VI) concentrations as a combined effect of aquifer heterogeneity and dynamic flow conditions. This study provides the first highly data‐constrained uranium transport simulations under highly dynamic flow conditions. It illustrates the value of reactive transport modeling for elucidating the relative importance of individual processes in controlling uranium transport under specific field‐scale conditions. Key Points: Successful simulation of a U(VI) tracer test under complex field conditions Relative importance of processes in controlling field‐scale U(VI) transport Insights into upscaling of uranium transport processes from laboratory to field